Global Soil Data Manager platform maintained and enhanced with data access functionalities - CGIAR Research Program on Water, Land and Ecosystems (2021)
Global Soil Data Manager is an online portal for use by researchers and development practitioners in sub-Saharan Africa to access geospatial soil databases and define sampling designs. The most used module is a sampling design to guide field data collection. It includes online user help.